2020
DOI: 10.3390/rs12182900
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Target Algorithm for Observing the Global Aerosol System: Past, Present, and Future

Abstract: The Dark Target aerosol algorithm was developed to exploit the information content available from the observations of Moderate-Resolution Imaging Spectroradiometers (MODIS), to better characterize the global aerosol system. The algorithm is based on measurements of the light scattered by aerosols toward a space-borne sensor against the backdrop of relatively dark Earth scenes, thus giving rise to the name “Dark Target”. Development required nearly a decade of research that included application of MODIS airborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 262 publications
(416 reference statements)
2
22
0
Order By: Relevance
“…Furthermore, the AOD trends are widespread, uniform and mainly occur over the SH oceans (Figure 1b). Positive AOD trends over the southern oceans are also apparent in Remer et al (2020; see their Figure 12). Since the CERES results do not show this unexpected behavior, we cannot exclude MODIS calibration drift as a possible cause, as recently suggested by Bellouin, Davies, et al (2020), who found similar results.…”
Section: Regional Zonal and Global Adre And Aod Trendsmentioning
confidence: 83%
“…Furthermore, the AOD trends are widespread, uniform and mainly occur over the SH oceans (Figure 1b). Positive AOD trends over the southern oceans are also apparent in Remer et al (2020; see their Figure 12). Since the CERES results do not show this unexpected behavior, we cannot exclude MODIS calibration drift as a possible cause, as recently suggested by Bellouin, Davies, et al (2020), who found similar results.…”
Section: Regional Zonal and Global Adre And Aod Trendsmentioning
confidence: 83%
“…The NASA GEOS is a global Earth system model that includes components for atmospheric circulation and composition, ocean circulation and biogeochemistry, land surface processes, and data assimilation (Rienecker et al, 2011). The coupled atmospheric constituent module within the GEOS architecture most relevant to this study is an aerosol module based on the Goddard Chemistry Aerosol Radiation Transport (GOCART) model (Colarco et al, 2010).…”
Section: Geos Simulations Of Aerosolmentioning
confidence: 99%
“…It can be identified on the monthly mean 0.55 micron AOD data from MODIS [15] on the NASA Terra satellite distributed via NASA Giovanni. The uncertainty in the AOD measured by this satellite is "τ=±0.05 ±0.15τ over land" and the AOD retrievals can be used in monitoring the aerosol radiative forcing of the global climate [16] [17].…”
Section: 4mentioning
confidence: 99%